ln x +ln (x+1) = ln 56

Thank you for the opportunity to help you with your question!

ln x + ln (x+1) = ln 56

ln( x(x+1) ) = ln 56

ln (x^2 + x) =ln 56

x^2 + x = 56

x^2 + x - 56 =0

x^2 + 8x -7x -56 = 0

x(x+8) -7(x+8)= 0

(x-7) (x+8) = 0

x-7 = 0 or x+8 =0

x= 7 or x= -8

thanks for answering my question , a no everything was perfect

WELCOME

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up